High-Frequency Electrodynamics of Slow Moving Media Taking into Account the Specular Reflection - Grinchik, N. N.; Boiprav, O. V. (Advanced Electromagnetics, 2021)
The paper presents the results of constructing the physical and mathematical model of high-frequency electromagnetic waves propagation in slowly moving media of finite dimensions, which takes into account the phenomena of specular reflection of these waves. The constructed model is based on formulas designed to determine the speed of electromagnetic waves propagation in slowly moving media of finite dimensions, as well as on equations designed to describe these waves. The advantageous feature of these equations is that they take into account the Fresnel drag coefficient for electromagnetic waves propagation speed. The approach to solving of these equations, as well as the approach to modeling of the process of electromagnetic waves propagation in slowly moving media of finite dimensions, based on the use of a difference scheme, in which the motion of these media is taken into account, is proposed. It has been determined that the proposed model and approaches can be used in solving problems related to the construction of receiving-transmitting paths, as well as in solving problems of aeroacoustics.